Visitors’ visiting motivation: Bako National Park, Sarawak - Kamria, Thalany; Radam, Alias (Elsevier Ltd. (ScienceDirect), 2013)
This study was conducted to analyse the visitors’ motives of visiting Bako National Park. A total of 564 local and foreign visitors were interviewed. Factor analysis with the varimax rotation method was employed to gain information from visitors on their behaviour reflecting their motives for ecotourism activities in the national park. The results showed that visitors visit a national park for four factors, which are challenge excursion, social trip, nature tour and getaway outing. This result may help the management authority to reposition national park attributes without neglecting the objectives of the national park existence. Several marketing implications also can be drawn from this study.